Implementasi Ice Breaking untuk Meningkatkan Konsentrasi Belajar Pada Siswa Kelas 3B MI Muhammadiyah 28 Surabaya - Fauzi, Muhammad Ilham Rifqyansya; Faradita, Meirza Nanda (J-SES : Journal of Science, Education and Studies, 2024)
Various problems occur in the learning process in the classroom at an early age, such as the concentration of students in learning is still low, mostly students cannot answer the teacher's questions and the method used by the teacher is only limited to lecture and question and answer methods. Learning model become a vehicle for educational interaction between teachers and students in learning activities teach, then one way to growing student concentration is by inserting ice breaking in the learning process whose purpose is to arouse enthusiasm is also interesting re-concentration as well as student attention. This study used descriptive qualitative method. This data collection technique uses interview techniques, observation, and documentation. The focus of this research is how to implement Ice Breaking in increasing the Learning Concentration of Class Students 3B MI Muhammadiyah 28 Surabaya and what are the inhibiting and supporting factors in the implementation of Ice Breaking in MI Muhammadiyah 28 Surabaya the conclusion that can be drawn is that the Application of Ice Breaking with the quiz method with prizes really helps students in increasing concentration during learning takes place because they do not feel pressured and make them feel happy with the Ice Breaking method in Learning. In terms of support, students are more prepared to do learning and understand more quickly than not using ice breaker during the learning process